The Effect of Empowerment and Performance on the Welfare of Kotabumi MSME - Selumo, Ari Yanto; Sari, Romida Rifiana; Hasan, Saukani; Eviatun, Esti (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research was conducted in Kotabumi City . 70 Kotabumi City MSME actors used as a sample in this research. This research uses descriptive qualitative as a research method, the aim of which is to find out the influence of MSME Empowerment and Performance on the Welfare of MSME Actors. To obtain data, questionnaires were distributed. After that, the data obtained will be processed using the Partial Least Square (PLS) method, which is a regression-based method. The results of this research show that the MSME Empowerment variable has a significant effect with t = 7.632613 > t table = 1.99089 on the MSME Performance variable, the MSME empowerment variable has a significant effect with t = 2.781585 > t table = 1.99089 on Welfare MSME Actor variable. And the relationship between the MSME Performance variables also has a significant effect because t = 5.839031 > t table = 1.99089 on the welfare of MSME actors . Keywords: Welfare, Performance, MSME, Empowerment